The Overnight Stay Tradition Following Engagement in Nagari Salareh Aia Utara, West Sumatra - Loenxy, Monica; Anhas, Ilham Agustian (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study examines the post-engagement overnight stay tradition (bamalam di rumah urang gadih) that continues to be preserved by the community of Nagari Salareh Aia Utara, Palembayan District, Agam Regency, West Sumatra. This tradition forms an integral part of the Minangkabau matrilineal kinship system, which positions women as the central axis of social and cultural structures. In practice, the prospective groom stays overnight at the bride-to-be’s family residence following the engagement ceremony. Although it holds significant symbolic meaning and social functions, certain aspects of the tradition have sparked debate, as they are perceived to be inconsistent with prevailing religious norms and moral values. The purpose of this research is to analyze the meaning, functions, and forms of adaptation of the tradition to ensure its alignment with customary principles while remaining consistent with Islamic legal provisions. The study adopts a qualitative approach with a field study design, employing participant observation, in-depth interviews with customary leaders, religious scholars, and community members, as well as an analysis of relevant Minangkabau literature. The findings reveal that the tradition serves three primary functions: (1) as a symbol of openness and social acceptance toward the prospective groom, (2) as an initial adaptation process for the groom-to-be to become acquainted with family norms and matrilineal customs, and (3) as a medium for assessing the character of the prospective groom. Over time, the community has implemented several adjustments, such as shortening the overnight stay duration, limiting direct interaction between the engaged couple, and replacing the practice with formal interfamily gatherings, thereby ensuring its conformity with religious values and contemporary social dynamics. This study asserts that the post-engagement overnight stay tradition is not merely a customary ritual but rather a dynamic form of social dialogue between generations, between customary law (adat) and Islamic law (syariah), and between local values and modernity. Accordingly, the community of Nagari Salareh Aia Utara demonstrates adaptive capacity in preserving its cultural heritage contextually, without compromising its identity as a religious customary society. [Penelitian ini mengkaji tradisi menginap pasca peminangan (bamalam di rumah urang gadih) yang masih dilestarikan oleh masyarakat Nagari Salareh Aia Utara, Kecamatan Palembayan, Kabupaten Agam, Sumatera Barat. Tradisi ini merupakan bagian dari sistem kekerabatan matrilineal Minangkabau yang menempatkan pihak perempuan sebagai pusat struktur sosial dan budaya. Dalam praktiknya, calon mempelai laki-laki menginap di rumah keluarga calon istri setelah prosesi peminangan. Meskipun memiliki makna simbolik dan fungsi sosial yang penting, tradisi ini memunculkan persoalan karena sebagian praktiknya dinilai kurang selaras dengan norma agama dan nilai kesusilaan yang berlaku. Penelitian ini bertujuan menganalisis makna, fungsi, dan penyesuaian tradisi ini agar tetap sesuai dengan tuntunan adat sekaligus selaras dengan prinsip syariat. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi lapangan, melalui observasi partisipatif dan wawancara mendalam terhadap tokoh adat, tokoh agama, dan anggota masyarakat, serta analisis terhadap berbagai literatur Minangkabau yang relavan. Hasil penelitian menunjukkan bahwa tradisi ini memiliki tiga fungsi utama: (1) sebagai simbol keterbukaan dan penerimaan sosial terhadap calon menantu laki-laki, (2) sebagai ruang adaptasi awal calon mempelai laki-laki dengan norma keluarga dan adat matrilineal, serta (3) sebagai ajang penilaian karakter. Dalam praktiknya, masyarakat telah melakukan berbagai bentuk penyesuaian, seperti mempersingkat durasi menginap, membatasi interaksi calon pengantin, hingga mengadaptasi tradisi tersebut dengan pertemuan formal antarkeluarga, demi menyesuaikan dengan tuntutan nilai-nilai keagamaan dan perubahan zaman. Penelitian ini menegaskan bahwa tradisi menginap bukan sekadar ritual adat, tetapi juga bentuk dialog sosial yang dinamis antara generasi tua dan muda, antara adat dan syariat, serta antara nilai-nilai lokal dan modernitas. Dengan demikian, masyarakat Nagari Salareh Aia Utara menunjukkan kapasitas adaptif dalam merawat warisan budaya secara kontekstual, tanpa kehilangan akar identitasnya sebagai bagian dari masyarakat adat yang religius.]